Expectativas e frustrações no processo de apadrinhamento de crianças em situação de acolhimento institucional - Sousa, Karollyne Kerol de (2010)
This research had as principal objective search for an understanding of the psychic mechanisms involved on the process of acting as a godfather of sheltered children. The practice of acting as a godfather is a voluntary service prevailing in some host institutions in Brazil. Although there is no legal definition for the term to act as a godfather , it can be described as a way to give children significant bonds, those which they should had with family members. It doesn t mean that works this way. It can be noticed that the practice of acting as a godfather has been used as a way to fill existential gaps on both sides. After a tour for the subjective constitution and for the movements of a contemporaneous person asked about happiness ideals, we analyzed a clinical case of a godson and four interviews with godmothers of sheltered children. The method used for the research and for the analysis was the psychoanalytic method. From analyzers listed in the clinical case and interviews, important data were constructed about the way of relationship fostered by the act of been godfather: the exaltation of volunteering practices, correlated with noble feelings like the goodness and the love for the other one; an exacerbated narcissism as an attempt to recover the omnipotence felt in the beginning of life; the seduction that permeates the relationship between the godfather and godson; the ambivalence of feelings aroused in this relationship; and similarities of the act of been a godfather with the adoption process, according to the search for the ideal son, that extends to the search of the ideal godfather and the ideal godson.